Responsibility as a social capital phenomenon in the eyes of young people. International perspective - Krzywosz-Rynkiewicz, Beata (Socialinė teorija, empirija, politika ir praktika, 2013)
Department of Psychology of Development and EducationSocial Science FacultyUniversity of Warmia and Mazury in Olsztyn, ul. Oczapowskiego 210-975 Olsztyn, PolandIn this article, we analyse the phenomenon of responsibility and its understanding among young people from Visegrad countries (Poland, Czech Republic, Slovakia, and Hungary). Using the AGA research method, 400 students of the last stages of economic faculties in capital and local universities were examined. The results indicate a personal rather than a social dimension of responsibility. We also found some patterns to depend on the country. Young Poles’ responsibility is more related to the subjective dimension, Hungarians’ to social, Czechs’ to affective, and Slovaks’ to moral one.Key words: responsibility, young people, social capital.Jaunimo požiūris į atsakomybę kaip į socialinį kapitalą . Tarptautinė perspektyvaBeata Krzywosz-RynkiewiczSantraukaŠiame straipsnyje analizuojama, kaip jaunimas iš Vyšegrado šalių (Lenkijos, Čekijos, Slovakijos, Vengrijos) supranta atsakomybę. Naudojant AGA metodą buvo ištirta 400 skirtingų universitetų studentų, besimokančių paskutiniuose ekonomikos fakultetų kursuose. Tyrimo rezultatai atskleidė, kad atsakomybė labiau suvokiama asmeniniu, o ne socialiniu lygmeniu. Be to, egzistuoja skirtumai tarp šalių.Pagrindiniai žodžiai: atsakomybė, jaunimas, socialinis kapitalas.